Pectate lyase activity of different species of pectobacteria when infecting potato stems and tubers - Shao , Chengyue; Evtushenkov, Anatoli N. (Experimental Biology and Biotechnology, 2024)
Pectate lyase activity is the most important virulence factor of phytopathogenic bacteria of the genus Pectobacterium. A high level of pectate lyase activity was detected in the tissues of potato stems affected by pectobacteria, it was several times exceeded the level of pectate lyase activity in macerated tissues of potato tubers, which may be due to the different biochemical composition of the tissues. The dependence of pectate lyase activity in the tissues of potato tubers on the plant variety was revealed. The pectate lyase activity of P. carotovorum, P. parmentieri, P. brasiliense and P. atrosepticum was significantly higher in the affected tuber tissues of the Vineta variety compared to that in the affected tuber tissues of the Palac variety. The highest levels of pectate lyase activity were recorded when potato tubers were infected with P. brasiliense, and the lowest – when potato tubers were infected with P. parmentieri. The resistance of potato tubers to the macerating action of pectobacteria is associated with the species of the phytopathogen. Potato tubers of the Palac variety turned out to be more resistant to the macerating effect of P. carotovorum and P. parmentieri, but less resistant to the macerating effect of P. brasiliense compared to potato tubers of the Vineta variety. Potato stems of the Vineta variety were less affected by the black stem than potato stems of the Palaс variety.